2016
DOI: 10.1016/j.shaw.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Work Pressure and Safety Behaviors among Health Workers in Ghana: The Moderating Role of Management Commitment to Safety

Abstract: Backgroundsafety and healthy working environment has received numerous research attention over the years. Majority of these researches seem to have been conducted in the construction industry, with little attention in the health sector. Nonetheless, there are couple of studies conducted in Africa that suggest pressure in hospitals. Therefore the aim of the study was to examine how pressure influence safety behavior in the hospitals. With reference to the relevance of safety behavior in primary health care deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…In 2006, a study conducted among 50 medical personnel, ranging from medical students to consultants in one of the leading teaching hospitals in Ghana, the Korle-bu teaching hospital in Accra, suggested a gap in actual knowledge of SPs and practice [ 14 ]. A study conducted among 422 HCWs in the Greater Accra Region of Ghana revealed that HCWs who had adequate knowledge in the area of safety and health were more likely to comply with SPs [ 15 ]. Another study that examined knowledge and awareness levels of 108 nurses in the Tamale Metropolis of Ghana on exposure to the hepatitis B virus and the risk of infection ascertained that the majority of nurses (94.4%) considered themselves susceptible to HBV infection yet very few had adequate knowledge of post exposure prophylactic treatment against HBV [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, a study conducted among 50 medical personnel, ranging from medical students to consultants in one of the leading teaching hospitals in Ghana, the Korle-bu teaching hospital in Accra, suggested a gap in actual knowledge of SPs and practice [ 14 ]. A study conducted among 422 HCWs in the Greater Accra Region of Ghana revealed that HCWs who had adequate knowledge in the area of safety and health were more likely to comply with SPs [ 15 ]. Another study that examined knowledge and awareness levels of 108 nurses in the Tamale Metropolis of Ghana on exposure to the hepatitis B virus and the risk of infection ascertained that the majority of nurses (94.4%) considered themselves susceptible to HBV infection yet very few had adequate knowledge of post exposure prophylactic treatment against HBV [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results of the study indicate that work stress is negatively correlated with safety behavior [11].…”
Section: Attentionmentioning
confidence: 81%
“… Negative attitudes and habits of the workers. -Job factors:  The workload increases the work pressure that affects negatively safety behavior of the workers (Amponsah-Tawaih and Adu, 2016). This may lead to potential OWRIs (e.g.…”
Section: Discussionmentioning
confidence: 99%